Resilience and strategic management: ways to ensure economic and social security of Ukrainian enterprises during long-term warfare - Viktor Alkema; Pavlo Hryhoruk; Halyna Skhidnytska; Oleksandr Sylkin (Clío)
The objective of the research is to discuss the strategies that companies in Ukraine can implement to maintain their resilience and simultaneously ensure their sustainability in an environment of protracted war. To achieve this objective, a qualitative methodology is employed that combines the hermeneutics of in-depth interviews with business leaders and case studies of two conflict-affected but truly resilient companies. This methodology allows the identification of best practices in crisis management, as well as the necessary adaptation policies in business models to face the growing economic and social challenges. The documentary sources consulted underline the importance of international cooperation, technological innovation, and the development of a favorable regulatory framework to foster business resilience and ensure operational continuity in a context of uncertainty and risk. It is concluded that resilience and strategic management are fundamental to ensure the economic and social security of Ukrainian companies in the context of war, but they are also universal principles that, for what they represent, can be useful to overcome crises of various kinds that threaten the survival of a company located in each time and space.